Interface Oral Health Science 2014 Innovative Research on Biosis-Abiosis Intelligent Interface - Sasaki, Keiichi; Suzuki, Osamu; Takahashi, Nobuhiro (Springer Japan : Imprint: Springer, 2015)
The Tohoku University Graduate School of Dentistry first introduced the concept of "Interface Oral Health Science", designed to establish and maintain healthy oral cavities, which are home to a number of mixed systems. Included in those systems are: (1) host tissues such as teeth, mucosa, muscle and bone, (2) parasites and microorganisms cohabiting the surfaces of the oral cavity, and (3) biomaterials that are used for the rehabilitation of oral functions. In addition, (4) these systems are subject to severe and complex mechanical forces. Therefore, it is critical to promote dental studies that integrate a wide range of interdisciplinary research as medicine, agriculture, material science, engineering, and pharmacology. With this incentive, international symposiums for interface oral health science have been held several times in the past. The concept has since refined and expanded, the result being the "Biosis-Abiosis Intelligent Interface," and projects aiming at the creation of highly functional and autonomic intelligent interfaces are ongoing. This book brings together a number of studies on incentives and projects by leading authors. Topics include biosis-abiosis interface of dental implants, biomaterials in interface science, biomedical engineering interface, and cell manipulation and tissue regeneration. Readers not only from the field of dentistry but also many related areas will find this book a valuable resource.